A Highly Ordered Quantum Dot Supramolecular Assembly Exhibiting Photoinduced Emission Enhancement. Issue 12 (10th February 2021) - Yamauchi, Mitsuaki; Yamamoto, Seiya; Masuo, Sadahiro
Abstract: Multicomponent supramolecular assembly systems enable the generation of materials with outstanding properties, not obtained from single‐component systems, via a synergetic effect. Herein, we demonstrate a novel supramolecular coassembly system rendering highly ordered quantum dot (QD) arrangement structures formed via the self‐assembly of azobenzene derivatives, where the photocontrollable photoluminescence (PL) properties of the QDs are realized based on photoisomerization. Upon mixing the assembled azobenzene derivatives and QDs in apolar media, a time‐evolution coaggregation into hierarchical nanosheets with a highly ordered QD arrangement structure occurs. Upon photoirradiation, the nanosheets transform into ill‐defined aggregates without arranged QDs together with enhancing the PL intensity. In days, the photoirradiated coaggregates undergo recovery of the PL properties corresponding to the arranged QDs through thermal isomerization. Abstract : The highly ordered coaggregates of quantum dots (QDs) with inter‐QD interaction can be created by using the self‐assembled azobenzene derivatives. Furthermore, the inter‐QD interaction can be reversibly controlled by photoirradiation and time‐aging.